The Effectiveness of Using SQ4R Technique in Learning English to Increase Students’ Reading Comprehension of 8th Grade at MTsN3 OKU Selatan - Ayu Gestia; Nurul Afifah; Trisilia Devana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja, 2024)
The researcher focused on knowing that the use of SQ4R technique has a significant effect on students’ reading comprehension. The design of this study was pre-experimental research. In this research, the researcher used the cluster random sampling technique. The sample for this research was eighth-grade students from 8B, which consists of 32 students. The kind of test given in this research was multiple choice, which consisted of 20 questions and was valid for the pre-test and post-test. The data was analyzed by using a sample paired T-test. The result of the analysis showed that the use of sq4rtechnique to increase students’ reading comprehension was good benefits. The result of the pre-test score was 42,65, and the post-test score after the treatment was 67,65. The testing of the hypothesis also proved that SQ4R technique had a significant effect on students’ reading comprehension. The significance value(2-tailed) showed that the value of Sig =0.000 was less than the significance level (α = 0.05), sig (2-tailed) 0.000 < 0.05. From the result, it can be concluded that SQ4R technique can be used as a medium to improve students’ reading comprehension.